1990
DOI: 10.1172/jci114760
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental isodisomy 6 associated with deficiency of the fourth component of complement.

Abstract: We identified an extremely rare condition, isolated complete deficiency of the fourth component of complement, in a child with systemic lupus erythematosus. The genes for C4 are located within the major histocompatibility complex (MHC) on the short arm of chromosome 6. The patient expressed only paternal phenotypes for proteins encoded by the MHC (HLA and GLO), yet was 46XX with no detectable 6p deletion.Genomic DNA from patient, parents, and sibling was digested with restriction enzymes, and blots were probed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…Differences in chromatin structure as well (Rabin et aL, 1987). The observation that paternal (Welch et aL, 1990) and maternal UPD 6 (van den Berg-Loonen et aL, submitted for publication) are compatible with nor mal human development supports our previous finding that the IGF2R gene is not imprinted (Kalscheuer et aL, 1993) and raises the possibility that this holds for the MAS gene, too. Expression and methylation studies should soon clarify this point and may shed more light as in the absence or presence of a trans-acting factor on the role of gene-specific and regional factors in the acting as a repressor by binding to the hypomethylated control of parent-specific expression, paternal CpG 2 region may account for the differential expression of the human and mouse IG F2R genes.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allesupporting
confidence: 77%
See 2 more Smart Citations
“…Differences in chromatin structure as well (Rabin et aL, 1987). The observation that paternal (Welch et aL, 1990) and maternal UPD 6 (van den Berg-Loonen et aL, submitted for publication) are compatible with nor mal human development supports our previous finding that the IGF2R gene is not imprinted (Kalscheuer et aL, 1993) and raises the possibility that this holds for the MAS gene, too. Expression and methylation studies should soon clarify this point and may shed more light as in the absence or presence of a trans-acting factor on the role of gene-specific and regional factors in the acting as a repressor by binding to the hypomethylated control of parent-specific expression, paternal CpG 2 region may account for the differential expression of the human and mouse IG F2R genes.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allesupporting
confidence: 77%
“…Our results clearly demonstrate th a t the region comprising CpG 2 is methylated in a parent-specific manner. viously described patients with uniparental disomy (UPD), one with unipaternal disomy and the other with unimaternal disomy for chromosome 6 (Welch et al} 1990; van den Berg-Loonen et a l., submitted for publi cation).…”
Section: -------------------------------41 -------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…These included all 7 familial cases (families K and L) and 4 sporadic cases ( (16,17), and 9 were identified using quantitative PCR of ESTs and STSs from the region (Fig. 1, ID [12][13][14][15][16][17][18][19][20]. Determining the parental origin in 9 of the duplication cases (visible and submicroscopic) was possible by testing both parents using the same method as that used for the probands.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 further cases with TND and paternal UPD6 have since been reported in the literature (8)(9)(10)(11)(12), and another involved a child with diabetes who died at the age of 16 days (13). The association is now firmly established, although 2 cases of paternal UPD6 have been reported in older patients with no early history of TND, which cannot yet be explained (14,15). We and others have subsequently shown that several nondisomic children with TND have paternally inherited duplications within the long arm of chromosome 6 (6q23-24) (12,(16)(17)(18).…”
mentioning
confidence: 99%